Pesantren Caretaker Strategies for Enhancing Qur’anic Memorization Motivation among Madrasah Ibtidaiyah Students - Edi Prayitno; Rido Kurnianto; Syamsul Arifin; Aldo Redho Syam; Olivia Ramandani (Jurnal Manajemen Pendidikan, 2025)
Background: The challenge of sustaining young students' motivation for Qur'anic memorization in integrated Islamic educational settings remains underexplored, particularly regarding institutional strategies within pesantren-based elementary schools. Purpose: This study aims to explore the strategies employed by pesantren caretakers to enhance Qur'anic memorization (tahfidz) motivation among students at MI Pesantren Anak Sholeh Baitul Qur'an Gontor, Ponorogo, East Java. Design/method/approach: Drawing on a qualitative case study design, data were gathered through semi-structured interviews with seven informants including the school principal, tahfidz coordinators, tahfidz teachers, parents, and students supplemented by participant observation and documentary analysis. Data analysis followed the interactive model of Miles, Huberman, and Saldaña, involving data condensation, display, and conclusion drawing. Results: The findings reveal four principal motivational strategies systematically implemented by the pesantren caretakers: (1) the Tahfidz Excellent Group, which cultivates pride and healthy competition; (2) Financial Incentive Awards for students exceeding memorization targets; (3) Munaqosyah examinations and Hubbul Qur'an graduation ceremonies involving parental participation; and (4) Tahfidz Camp as a supplementary immersive program. These strategies generate tangible motivational outcomes, including heightened memorization consistency, strengthened self-discipline, robust parental engagement, and positive behavioral changes both within the school and home environments. Contribution/value: This study contributes to the growing body of scholarship on Islamic educational management by illuminating how institutional-level motivational architecture within pesantren settings can effectively sustain young learners' commitment to Qur'anic memorization.